2013
DOI: 10.1371/journal.pone.0060374
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin-Containing Diet Causes Oxidative Stress in the Mouse

Abstract: Mycotoxins which mainly consist of Aflatoxin (AF), Zearalenone (ZEN) and Deoxynivalenol (DON) are commonly found in many food commodities. Although each component has been shown to cause liver toxicity and oxidative stress in several species, there is no evidence regarding the effect of naturally contained multiple mycotoxins on tissue toxicity and oxidative stress in vivo. In the present study, mycotoxins-contaminated maize (AF 597 µg/kg, ZEN 729 µg/kg, DON 3.1 mg/kg maize) was incorporated into the diet at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 30 publications
(33 reference statements)
4
61
1
Order By: Relevance
“…Mycotoxins such as aflatoxins, deoxynivalenol and zearalenone which are commonly found in animal feeds have been suggested to induce oxidative stress in animals (Hou et al, 2013).…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…Mycotoxins such as aflatoxins, deoxynivalenol and zearalenone which are commonly found in animal feeds have been suggested to induce oxidative stress in animals (Hou et al, 2013).…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…[22] The primary antioxidant enzymes responsible for protection from oxidative stress are superoxide dismutase (SOD) and glutathione peroxidase (GPx). [24] Recent studies confirmed direct dose-dependent effect of T-2 toxin on granulosa cells proliferation and steroidogenesis. As far as we know, there are no studies investigated an impacts of T-2 toxin in combination with natural antioxidant quercetin on porcine granulosa cells antioxidant status in vitro.…”
Section: Introductionmentioning
confidence: 80%
“…We found that LPS led to mononuclear cell infiltration and fatty degeneration in the liver. AST catalyzes the reversible transfer of an amino group between aspartate and glutamate, and as such, is an important enzyme in the amino acid metabolism (Hou et al, 2013). AST and ALT are commonly measured clinically as markers of liver health, and thus the enhanced AST and ALT activities in the serum after 6, 12, 24 and 36 hr of LPS treatment indicated that LPS could lead to the organ pathology changes and liver damage, while the histopathological changes in the liver certified this deduction.…”
Section: Discussionmentioning
confidence: 99%
“…The possible interpretation for this observation is that the metabolism of LPS mainly occurs in the liver, and these three anti-oxidative enzymes cooperate as follows: SOD catalyzes the dismutation of the superoxide radical (O 2-) to oxygen peroxide (H 2 O 2 ), protecting the organs from the O 2-damage. GPx catalyzes the reduction of H 2 O 2 in water (Hou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation